ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PEMANFAATAN DAN PENGGUNAAN SISTEM E-TICKET (Studi Empiris pada Biro Perjalanan di Kota Semarang) - Jati, Nugroho Jatmiko; Laksito, Herry (Diponegoro Journal of Accounting, 2012)
Appropriate use of information technology will enable the company to gain advantage and improve the performance of every employee. The purpose of this study was to examine the factors that influence interest in the utilization of information technology and its impact on the use of information technology to test the model proposed by Venkatesh, et al. (2003) is a model Unified Theory of Acceptance and Use of Technology (UTAUT). This study used a sample of 15 travel agencies and travel agency listed on the city of Semarang in Central Java and apply ASITA e-ticket service in terms of travel ticket reservation. Determination of the sample made ​​with convenience sampling method. Data were collected using a questionnaire that is sent directly to each company (primary data). A total of 134 questionnaires were returned from 150 sent and only 120 questionnaires that can be processed. Data analysis was done by using multiple regression with SPSS 17 software. These results indicate that the performance expectations and business expectations of a positive effect on interest in the utilization of information technology. Conditions that facilitate the user's interest in the utilization of information technology and positive influence on the use of information technology. Only the social factors that not influence the use of information technology interests. This is due to environmental influence, prestige, and social status did not affect the use of information technology.